HIV geospatially clusters with firearm trauma in 35 Atlanta zip codes. Issue 2 (1st February 2023) - Tracy, Brett M.; Swift, David A.; Smith, Randi N.
ABSTRACT: The purpose of this study was to assess if rates of firearm trauma within Atlanta geospatially clustered with HIV prevalence and new HIV diagnosis rates. We retrospectively reviewed our Atlanta trauma center's registry for patients sustaining a ballistic firearm trauma from 2014 through 2018. Using the patient's zip code of home residence, we determined the rate of firearm trauma for that zip code. We obtained publicly available rates for HIV that corresponded with these select zip codes to perform a geospatial cluster analysis. The cohort was comprised of 1495 patients and represented 35 zip codes in Atlanta. The mean rate of firearm trauma for the 35 zip codes was 171.1 (±296.4) per 100, 000 people. Compared to all Atlanta, the 35 zip codes' mean HIV prevalence (1863.9 vs 924.1, p  < .0001) and new HIV diagnosis rate (396.9 vs 199.7, p  < .0001) were significantly higher. Rates of firearm trauma and HIV prevalence demonstrated significant geospatial clustering (β 0.38, 95% CI 0.22-0.53, p  < .0001) as did rates of firearm trauma and new HIV diagnoses (β 0.36, 95% CI 0.18-0.54, p  = 0.0002). Our findings provide granular geographic data that could guide targeted HIV screening efforts in communities where our firearm-injured patients live.